1994
DOI: 10.1016/0014-5793(94)01119-2
|View full text |Cite
|
Sign up to set email alerts
|

Troponin T is capable of binding dystrophin via a leucine zipper

Abstract: Using genetic and physical assays for protein-protein interactions, we identified a fast isoform of troponin T that binds to dystrophin. Troponin T specifically bound to the first of two highly conserved leucine zipper motifs in the carboxy terminus of dystrophin [1,2]. Single amino acid changes in the zipper predicted to disrupt a-helix formation or cause steric hindrance abolished this binding. These data support the hypothesis that dystrophin couples the contractile apparatus to the sarcolemma and indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Hence, the role of the HR motif in TnT-TnI binary interaction has not been established prior to this study. Recently, it was reported that fast skeletal TnT binds to dystrophin by coiled coil-or leucine zipper-mediated interaction (29). However, the in vivo relevance of this finding is not clear, and the authors also did not investigate what region of TnT was involved in the interaction with dystrophin.…”
Section: Discussionmentioning
confidence: 52%
“…Hence, the role of the HR motif in TnT-TnI binary interaction has not been established prior to this study. Recently, it was reported that fast skeletal TnT binds to dystrophin by coiled coil-or leucine zipper-mediated interaction (29). However, the in vivo relevance of this finding is not clear, and the authors also did not investigate what region of TnT was involved in the interaction with dystrophin.…”
Section: Discussionmentioning
confidence: 52%
“…However, anity absorption is not mediated by a classical leucine zipper interaction. Leucine zipper domains play a well-documented role in facilitating homodimer and heterodimer formation with many dierent proteins, including transcription factors (Hurst, 1994), cellular kinases (Ruth et al, 1997;Gamm et al, 1995;Kitigawa et al, 1995), transmembrane receptors (Saras et al, 1994;Klein et al, 1993;Rodrigues and Park, 1993;Chen et al, 1993;Earl et al, 1993) and cytoskeletal proteins (Klein et al, 1993;Bikle et al, 1996;Pearlman et al, 1994;Ward and Kirshner, 1990;Maekawa and Kuriyama, 1993). The mechanism for dimer formation by leucine zippers requires hydrophobic interactions between opposing leucine residues in the heptad repeats, which may be stabilized by charge interactions (Hodges, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…A 91-bp-long residue sequence that includes two sequences corresponding to structures referred to as the "leucine zippers," which are typical of several gene regulatory proteins (33,34), is located between the coiled-coil region and the collagenous stretch. This finding is rather unusual especially for an ECM protein, as there are only a few precedents in the literature for the presence of leucine zippers in the extra nuclear compartments: the Drosophila ECM protein pollux (35) and the cytoplasmic protein dystrophin, whose leucine zipper has been reported to interact with troponin (36). Although the leucine zipper pattern is far from being specific, it is not clear at the moment what might be the significance of its presence in the context of EMILIN.…”
Section: Purification and Peptide Sequences Of Chick Emilin-amentioning
confidence: 95%